2020
DOI: 10.1111/inm.12705
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of risks for occupational hazards in patient seclusion and restraint practices in psychiatric inpatient care: A focus group study

Abstract: Seclusion and restraint are regularly used to manage patient aggression events in psychiatric inpatient care, despite occupational safety concerns. There is currently a lack of information on how nurses perceive the use of patient seclusion and restraint as a risk for occupational safety. The aim of this study is to describe the risks for occupational hazards in patient seclusion and mechanical restraint practices as well as ideas for improvement identified by nurses. A qualitative descriptive design was adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Of these, subsequent review or debriefing with professionals and users was highlighted for the reconstruction of beliefs, attitudes and behaviours that produce a less restrictive team culture (Chambers et al, 2015; Giacchero‐Vedana et al, 2018; Martello et al, 2018). Some interviewees agreed with findings reported by Muir‐Cochrane et al (2018), Laukkanen et al (2019), Varpula et al (2020) and Obay and Ferial (2019), expressing their concerns about withdrawing or banning mechanical restrictions as this would leave them without tools to address the situations that most compromised safety. The main barrier identified by the professionals interviewed was the lack of personnel (McKeown et al, 2019), which impacted the possibility of having more contact and time with users to achieve a strong therapeutic relationship that would facilitate effective verbal de‐escalation with long‐lasting results.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Of these, subsequent review or debriefing with professionals and users was highlighted for the reconstruction of beliefs, attitudes and behaviours that produce a less restrictive team culture (Chambers et al, 2015; Giacchero‐Vedana et al, 2018; Martello et al, 2018). Some interviewees agreed with findings reported by Muir‐Cochrane et al (2018), Laukkanen et al (2019), Varpula et al (2020) and Obay and Ferial (2019), expressing their concerns about withdrawing or banning mechanical restrictions as this would leave them without tools to address the situations that most compromised safety. The main barrier identified by the professionals interviewed was the lack of personnel (McKeown et al, 2019), which impacted the possibility of having more contact and time with users to achieve a strong therapeutic relationship that would facilitate effective verbal de‐escalation with long‐lasting results.…”
Section: Discussionsupporting
confidence: 65%
“…Regarding the professional, there was some controversy over gender, although Varpula et al (2020) stated that the approach to an agitated patient should be based on compassion and care rather than a display of strength. Korkeila et al (2016) reported that the more experience nurses have, the more effective the alternatives to MR for patients with psychomotor agitation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, nurses emphasized security issues in patient care, such as having more guards and safety measures. Similarly, a Finnish study found that the development of aggression management in nurses’ work focused on better camera surveillance and personal alarm systems [ 43 ]. Nurses may currently prioritize the management of aggressive events in their work, whereas patients and families focus on the origins of aggression and how to prevent aggressive events.…”
Section: Discussionmentioning
confidence: 99%
“…When participants were comfortable talking (Olsson Möller et al, 2020), the interaction among the participants would help to explore and clarify the participants' experiences and views concerning the study aims (Nybergh et al, 2020). This method might help gather wealth materials from the interaction between participants (Nord et al, 2020;Varpula et al, 2020) and generate rich research data from the discussion (Djohari et al, 2020;Nord et al, 2020;Varpula et al, 2020).…”
Section: Focus Group Less Adopted In E-commerce Researchmentioning
confidence: 99%